Investigating recycled 3D printing filament waste-based composites reinforced by fillers - Amged Elhassan; Sidra Siraj; Noura Al Mazrouei; Waleed Ahmed; Essam Zaneldin; Ali H. AlMarzouqi (Academia Materials Science)
This study explores the potential of recycling different waste generated from 3D printing (3DP) filaments to develop composite materials integrated with silica filler. Through comprehensive mechanical property analyses, including tensile stress, ductility, and toughness, the research exposes significant trends associated with varying concentrations of silica filler. Results indicate a substantial increase in stiffness as silica filler content rises, owing to enhanced interfacial adhesion properties. However, this enhancement is accompanied by diminished ductility and toughness due to the formation of agglomerates and structural voids within the composite matrix. These findings highlight the critical importance of optimizing filler dispersion and concentration to balance mechanical performance and material sustainability in recycled 3DP filament waste-based composites.